Online Identity as a Psychological Phenomenon: Contemporary Approaches and Empirical Research - A.N. Nevryuev; N.V. Samorodov; O.V. Smirnikova (Современная зарубежная психология)
Context and Relevance. Amid the rapid digital transformation of society, research in personality psychology that focuses on its online dimensions is gaining particular relevance. One such dimension is the concept of an individual's online identity. Objective. To analyze international research dedicated to the study of online identity, identify key areas of focus, and describe the implications associated with the formation, development, and transformation of this phenomenon. Review Methodology. A search for peer-reviewed articles was conducted in international databases (Scopus, Web of Science, PsycINFO) covering the period from 2019 to 2024, using the following keywords: “online identity,” “digital self,” “social identity online,” and “virtual identity.” A total of 37 articles were initially identified. After screening (e.g., lack of full text, journal not relevant to the field of psychology), 25 articles were selected for further analysis. Results. Context and Relevance. Amid the rapid digital transformation of society, research in personality psychology that focuses on its online dimensions is gaining particular relevance. One such dimension is the concept of an individual's online identity. Objective. To analyze international research dedicated to the study of online identity, identify key areas of focus, and describe the implications associated with the formation, development, and transformation of this phenomenon. Review Methodology. A search for peer-reviewed articles was conducted in international databases (Scopus, Web of Science, PsycINFO) covering the period from 2019 to 2024, using the following keywords: “online identity,” “digital self,” “social identity online,” and “virtual identity.” A total of 37 articles were initially identified. After screening (e.g., lack of full text, journal not relevant to the field of psychology), 25 articles were selected for further analysis. Results. Findings indicate that there are both positive and negative aspects of the relationship between online identity and individuals’ personal and socio-psychological characteristics. Furthermore, various outcomes related to online identity are linked to behavior both within digital environments and beyond them. Conclusions. Online identity can function as a complement to offline identity, but it can also distort it. Different digital environments bring both positive and negative consequences for various types and characteristics of online identity. Social identity plays a crucial role in behavioral choices (e.g., prosocial vs. aggressive behavior) and related decision-making processes. Parental identity in the online space is of particular significance in the study of this phenomenon. A search for peer-reviewed articles was conducted in international databases (Scopus, Web of Science, PsycINFO) for the period from 2019 to 2024 using the following keywords: "online identity", "digital self", "social identity online", and "virtual identity". Initially, 37 articles were identified. After applying selection criteria (e.g., no full text available, the journal is not listed in psychological databases), 25 articles were included in the final analysis. Results. It was found that both positive and negative aspects exist in the relationship between online identity and personal or socio-psychological characteristics of individuals. Furthermore, a range of consequences for online identity were identified, which are connected to a person’s behavior both in digital spaces and beyond them. Conclusions. Online identity can either complement or distort offline identity. Different digital environments offer both positive and negative opportunities for its development. Social identity plays a key role in behavior choice (prosocial or aggressive) and decision-making related to it. Parental identity in online spaces also represents a significant area of interest in studying this phenomenon.